A monotonically declining elevational pattern of bacterial diversity in freshwater lake sediments. (13th October 2016) - Zeng, Jin; Zhao, Dayong; Li, Huabing; Huang, Rui; Wang, Jianjun; Wu, Qinglong L.
Summary: The distribution patterns of bacterial communities along elevational gradients remain unexplored in aquatic ecosystems. This study investigated the diversity and community composition of bacteria in the sediments of lakes along a mountainside elevational gradient from 525 to 4 490 m in western China. The bacterial alpha diversity (taxonomic richness and phylogenetic diversity) at different sediment depths decreased monotonically with the increasing elevation, and the beta diversity (dissimilarity between lakes) increased significantly with the increasing elevation distance. Both elevation and chemical variables including pH and carbon/nitrogen ratio were identified as major factors affecting the bacterial diversity. Especially, bacterial alpha/beta diversity was significantly related to both chemical and elevational gradients in the surface sediments, whereas elevation overwhelmed chemical factors in influencing the bacterial alpha/beta diversity in the subsurface sediments. Phylogenetic structure analysis demonstrated that environmental filtering was the most important process affecting the bacterial community assembly along the elevational gradient, and the strength of environmental filtering increased towards high elevations. In summary, we observed for the first time a monotonically decreasing elevational pattern in bacterial diversity of freshwater lake sediments, which is mainly driven by elevation associated environmental factors.